Chemical characterization and bioactivity of the most widely appreciated cultivated mushrooms: studies in fruiting bodies and mycelia - Reis, Filipa S. (2012)
More than 3000 mushrooms are said to be “prime edible species”, of which only 100 are cultivated commercially, and only ten of those on an industrial scale. The most cultivated mushroom worldwide is Agaricus bisporus followed, among others, by Lentinula edodes and Pleurotus spp. [1]. The present work reports and compares the nutritional value, bioactive compounds and antioxidant properties of highly consumed fresh cultivated species: Agaricus bisporus (White and Brown mushrooms), Pleurotus ostreatus (Oyster mushroom), Pleurotus eryngii (King oyster mushroom) and Lentinula edodes (Shiitake) [2,3]. Nutritional value was accessed through the composition in macronutrients determined following standard procedures; individual profiles in sugars and fatty acids were obtained by HPLC-RI and GC-FID, respectively. Micronutrients such as tocopherols were analysed by HPLC-fluorescence. Moreover, both fruiting bodies and mycelia produced in vitro were submitted to antioxidant potential evaluation (free radicals scavenging activity, reducing power and lipid peroxidation inhibition in cell homogenates) and phenolic compounds characterization by HPLC-DAD/MS. Shiitake revealed the highest levels of macronutrients, unless proteins, as also the highest sugars, tocopherols and polyunsaturated fatty acids (PUFA) levels, and the lowest saturated fatty acids (SFA) content. The highest antioxidant potential was shown by Agaricus bisporus (brown). Regarding the mycelia, Lentinula edodes was the species with highest antioxidant properties. Comparing mushrooms with the corresponding mycelium, in general, the species in vivo revealed highest antioxidant activity than the in vitro samples. This study contributes to the elaboration of nutritional databases of the most consumed mushroom species worldwide, allowing comparison between them and their mycelia obtained in vitro, which can be used for the biotechnological production of compounds with biological interest.